Coating of L-Arginine Modified Silica on Magnetite through Two Different Sol-Gel Routes - Amaria Amaria; Suyanta Suyanta; Nuryono Nuryono (Universitas Gadjah Mada, 2017)
In this research, magnetite coated with L-arginine modified silica (Fe3O4/SiO2-GPTMS-Arg) has been synthesized through a sol-gel process at a room temperature in two Routes. In Route 1, a precursor of sodium silicate solution (source of SiO2), 3-glycidoxypropyltrimethoxysilane (GPTMS) as a coupling agent and L-arginine (Arg) as the source of functional groups were added sequentially to magnetite nanoparticles (Fe3O4). Gelling was carried out by adding HCl solution dropwise to the mixture to reach pH of 7.0. The product was washed with water and ethanol and then dried at 65 °C for 1 day. In Route 2, sodium silicate solution was added to a mixture of GPTMS and L-arginine, and then the sol obtained was added into magnetite nanoparticles. The results were characterized with FTIR spectroscopy, X-ray diffraction, atomic absorption spectroscopy and volumetric method to identify functional groups, crystal size, iron ions released and amino groups content, respectively. The results showed that Fe3O4/SiO2-GPTMS-Arg has been successfully synthesized through both two routes. Route 1, however, gave product of Fe3O4/SiO2-GPTMS-Arg more stable and more content of amino groups than Route 2. The presence of amino groups leads to the application of the product for metal ion removal from aqueous solution.